TOM-Scale: a new method to programme training sessions loads in football - Muñoz López, A.; de la Cruz, B.; Naranjo, J. (Archivos de medicina del deporte, 2017)
There are several methods to control both the training and match load in football. However, most of these methods do not specify a clear methodology to pre-quantify this training or match load. The aim of this study was to develop a football specific training load monitoring scale (TOM-scale) to programme the session training load. 18 professional football players from the Latvian National Football Team were tracked throughout 466 football sessions, with individual sessions ranging from 13 to 24 for each player. Players were tracked using a multisensor device including a 5 Hz Global Positioning System, a 1000 Hz triaxial accelerometer and a heart rate monitor band. A football specific scale was developed to establish session training load prior to it. This scale is based on commonly football training tasks categories, with specific set parameters for each one. External training load variables involved total running distance, % of high intensity actions (> 14.4 km•h-1), number of accelerations and decelerations, sprints (> 21 km•h-1) and impacts. Internal training load variables were % heart rate maximum, Banister TRIMP and Edwards TRIMP. The results showed positive significant correlations (p < 0.05) from moderate (r > 0.40) to very large (r < 0.90) between TOM-scale training load and all the external and internal training load variables studied. In conclusion, although this new method does not avoid of controlling the real training load to assess the way the football players cope with the individual training loads, TOM-scale may be useful to programme football sessions and adopt a periodization strategy over the season to, in example, avoid non-functional overreaching phases and/or undesirable high isolated performance peaks.